Characterization of cellular immune response to chemically defined glycoconjugates from Leishmania mexicana subsp. amazonensis. - Rodrigues, M M (1986)
Two defined glycoconjugates (GP-10/20 and FR II Phe) purified from Leishmania mexicana subsp. amazonensis were analyzed with respect to their ability to induce cellular responses in immunized and infected mice. Each glycoconjugate was recognized by specific immune cells, as assessed by the proliferative response of lymph node cells of immunized mice. The response to GP-10/20 depended on helper T cells and antigen-presenting cells and was restricted by a major histocompatibility complex class II gene product. A specific anti-GP-10/20 T-cell line was established, and it was able to transfer a delayed-type hypersensitivity (DTH) response to normal mice. Both antigens were also recognized during an ongoing disease, as assessed by DTH response of infected mice. By this response, it was possible to distinguish susceptible from resistant strains of mice. In the course of the disease in resistant mice a correlation between the size of the primary lesion and the DTH response to GP-10/20 was observed. The presence of the glycoproteins on both promastigote and amastigote forms of the parasite, the antigenic similarities between both fractions, and the distribution of the GP-10/20 antigen in other trypanosomatids were studied. The results showed that both antigens were present on promastigotes and amastigotes. GP-10/20 shared no epitopes with FR II Phe, was included as part of the crude preparation leishmanin, and had some cross-reactive determinants with Leishmania donovani and Crithidia deanei.